Dynamic Ureas with Fast and pH‐Independent Hydrolytic Kinetics. Issue 29 (30th April 2018) - Cai, Kaimin; Ying, Hanze; Cheng, Jianjun
Abstract: Low cost, high performance hydrolysable polymers are of great importance in biomedical applications and materials industries. While many applications require materials to have a degradation profile insensitive to external pH to achieve consistent release profiles under varying conditions, hydrolysable chemistry techniques developed so far have pH‐dependent hydrolytic kinetics. This work reports the design and synthesis of a new type of hydrolysable polymer that has identical hydrolysis kinetics from pH 3 to 11. The unprecedented pH independent hydrolytic kinetics of the aryl ureas were shown to be related to the dynamic bond dissociation controlled hydrolysis mechanism; the resulting hindered poly(aryl urea) can be degraded with a hydrolysis half‐life of 10 min in solution. More importantly, these fast degradable hindered aromatic polyureas can be easily prepared by addition polymerization from commercially available monomers and are resistant to hydrolysis in solid form for months under ambient storage conditions. The combined features of good stability in solid state and fast hydrolysis at various pH values is unprecedented in polyurea material, and will have implications for materials design and applications, such as sacrificial coatings and biomaterials. Abstract : A class of dynamic hindered aromatic ureas (HAU) as the first example of hydrolysable polymers with pH‐independent hydrolytic kinetics is reported. The urea bond dissociation of HAU is two orders of magnitude faster than the reported aliphatic hindered ureas in organic solvent and among the fastest dynamic chemistries reported.